Pensions in Palestine : Reform in a Context of Unrest, Volume 1. Main Report - World Bank (Washington, DC, 2013)
At the request of the Palestinian Authority (PA), the status of pension schemes in the West Bank and Gaza was reviewed, and a technical analysis of the two civil service schemes was undertaken. A Technical Appendix reports in detail on projections of the financial status of the civil service schemes as well as on improvement options. This paper summarizes the main findings and highlights the policy implications. Its primary focus is on solutions that could be implemented in the short-term. The civil service pension schemes are bankrupt and in need of reform. The major issues facing them are: financial non-sustainability; government arrears in contributions; corporate governance issues resulting in rapid depreciation of the pension fund; the lack of financial disclosure; government overstaffing; and the lack of coverage for the private sector. This report recommends as critical next steps in the short term that there must be immediate and significant parametric reforms designed to restore financial solvency and enhance equity, such as reducing the retirement age and cutting benefit accrual rates. Governance, that is, increasing the transparency and efficiency of the Gaza Pensions and insurance Corporation (GPIC), the largest non-bank financial institution in the West Bank and Gaza, has been suggested. Right-sizing government employment is also important. In the long-term, systemic reforms will be needed to solidify pensions for government workers. Comprehensive protection for all elderly persons, one of the most vulnerable groups, is desperately needed within the context of the current crisis. A universal flat benefit scheme is the only short-term option that can provide broad-based assistance. Another short-term key concept is the recovery of pension transfers owed to Palestinian workers from Israel; the value could be significant and could avert poverty for many soon-to-retire Palestinians with extensive work histories in Israel. The sequencing and initiation of pension reform is a lengthy process, involving the reconciliation of conflicting priorities among different stakeholders. Within the context of the West Bank and Gaza, it may be best to think of the reform process in three steps: commitment building, coalition building, and implementation.